Assessment of quality of life during treatment of pediatric oncology patients - Prerna Batra; Birendra Kumar; Sunil Gomber; M S Bhatia (Wolters Kluwer Medknow Publications, 2014)
Background: The objective of this study was to assess health-related quality of life (HRQOL) of pediatric cancer patients and their parents in North India. Materials and Methods: Seventy-five cancer children were assessed for HRQOL, using Lansky play performance scale and health utility index-2 (HUI-2). Fifty-seven patients were followed-up after 4 months after therapy and reassessed. Their parents were also assessed using World Health Organisation (WHO) QOL BREF. Seventy five controls were also assessed and compared. Results: Lansky and HUI-2 scores of patients, as well as WHO QOL BREF of parents were significantly poor in cancer patients when compared to controls. There was significant improvement after therapy in patients with lymphomas and miscellaneous tumors. Pain and self-care were found to be maximally affected domains on HUI-2. Conclusions: Large prospective multicenter studies may be undertaken and hence that need based interventions can be planned.